Competitive Marketing Strategies for the Indian Pharmaceutical Industry-Post 2005: A Meta Analysis - Wadhwa, Navneet; Rodrigues, Lewlyn L. (Indian Journal of Marketing, 2004)
In 1970, the Indian Patent Act was introduced, which tilted the scales in favour of Indian companies, to freely develop, and patent alternative processes for products discovered and patented elsewhere. But now, with India committed to the WTO line on product patents, the rules of the pharmaceutical business in India are once again poised to witness a 180Â° paradigm shift. Given the backdrop of the momentous prospective changes, uncertainty looms over the prospects of the 23,000 players that the Indian pharmaceutical industry has. In the long term, the following new multi-dimensional pharmaceutical marketing models shall enable companies to create niches and develop core competence.